Produção de 2,3-butanodiol utilizando levedura recombinante de alta performance a partir de subprodutos do processamento de cana-de-açúcar - Dias, Renan Kiister (Universidade Federal de São Carlos, 2025)
In light of the global need to transition the current energy matrix, the development of integrated biorefineries emerges as a promising alternative by enabling the conversion of by-products into value-added compounds through sustainable processes. Among the abundantly available by products in Brazil, those derived from sugarcane processing—such as molasses and bagasse— are particularly noteworthy. 2,3-Butanediol (BDO) is a highly relevant chemical compound with a wide range of industrial applications and is traditionally produced via non-renewable routes. Its production from renewable sources represents a significant advance in terms of sustainability. In this context, the present study aimed to contribute to the development of a BDO production process using by-products from sugarcane processing and the recombinant yeast Saccharomyces cerevisiae HGS37. Initially, the performance of the strain was evaluated using molasses as the substrate. Despite exhibiting a slower metabolism compared to glucose due to the need for sucrose hydrolysis, the strain was able to produce 56.1 g/L of BDO with a productivity of 0.6 g/L/h when cultivated in molasses. Additionally, the nutrient-rich composition of molasses enabled the elimination of medium supplementation. Subsequently, process conditions were assessed through a 2³ factorial experimental design, varying initial optical density (OD₀ 5–50), pH (4–6), and initial ethanol concentration (5–40 g/L). The results indicated that the initial cell density significantly influenced BDO production, with the highest sugar conversion (69.5%) and BDO titer (54.67 g/L) achieved under conditions of OD₀ 50, pH 6, and 5 g/L ethanol. To further enhance cell loading, cell immobilization significantly improved the strain's performance in molasses, leading to remarkable BDO production (122.99 g/L) and productivity (1.28 g/L/h). The yeast also performed well in non-detoxified sugarcane bagasse hydrolysate, reaching 92.15% of the theoretical BDO yield. Finally, BDO production in an integrated process using both hydrolysate and molasses proved to be an effective strategy to achieve high BDO concentrations (above 100 g/L) in a shorter process time (reduced from 96 to 72 hours). These findings highlight the potential of the HGS37 strain and the technical feasibility of BDO production via fermentation using molasses and lignocellulosic hydrolysate as substrates.
Production of 2,3-butanediol using high-performance recombinant yeast from sugarcane processing by-products
Keywords: 2,3-Butanodiol; Biorrefinaria; Saccharomyces cerevisiae; Levedura recombinante; Melaço; Biomassa lignocelulósica; 2,3-Butanediol; Biorefinery; Recombinant yeast; Molasses; Lignocellulosic biomass; Saccharomyces cerevisiae; ENGENHARIAS::ENGENHARIA QUIMICA::PROCESSOS INDUSTRIAIS DE ENGENHARIA QUIMICA; ENGENHARIAS::ENGENHARIA QUIMICA